Cytomegalovirus‐associated thrombocytopenia treated with thrombopoietin receptor agonist. Issue 9 (16th September 2016) - Simpson, J. D.; Matthews, G. V.; Brighton, T. A.; Joseph, J. E.
Abstract : Symptomatic cytomegalovirus (CMV) in immunocompetent individuals is an uncommon, yet recognised, phenomenon. This report discusses a case of CMV‐associated thrombocytopenia refractory to immunomodulation and antivirals. Ultimately, a clinicopathological response was attained with eltrombopag. This is the first report of the efficacy of thrombopoietin receptor agonists in this context. This experience provides insight into possible pathogenic mechanisms of CMV‐associated thrombocytopenia and presents a therapeutic option.